From ligature treatment to reconstructive angiosurgery (to 250th anniversary of vessel suture) - A. V. Shteinle (Бюллетень сибирской медицины)
The historical review of the treatment of the injuries of the main arteries has been carried out by the author from the XVII century to the our time. The prime stages of the formations of the reconstructive surgery of the arteries have been shown.